Ritual Dynamics of the Sisingaan Tradition in the Panganten Circumcision Ceremony: A Victor Turner Theoretical Analysis - Murtado, Diran (Definisi: Jurnal Agama dan Sosial Humaniora, 2024)
This study explores the profound cultural and social significance of the sisingaan tradition in the Panganten Sunat ceremony in Cibiru District, Bandung City, Indonesia, through the lens of Victor Turner's ritual theory. Rooted in local customs, this tradition is not merely a form of entertainment but serves as a symbolic ritual of social transition, marking the passage from childhood to adulthood for individuals undergoing circumcision. Using a qualitative approach, the research highlights liminality—a transitional phase in which participants shift in social roles and identities. The findings reveal that the sisingaan tradition fosters an egalitarian sense of community (communitas), breaking down hierarchical barriers and reinforcing social solidarity and cohesion among participants. Through rich symbolic elements such as lion effigies, traditional music, and ceremonial processions, the ritual acts as a vehicle for preserving cultural heritage and strengthening the collective identity of the Cibiru community. The study concludes that the sisingaan tradition serves as both a cultural preservation mechanism and a social tool for teaching values to younger generations. Its contributions extend beyond the ceremonial, highlighting the role of traditional rituals in fostering unity, maintaining cultural integrity, and shaping societal structures.